Determinants of Quality of Life According to Cognitive Status in Parkinson’s Disease - Fan, Yun; Liang, Xiaoniu; Han, Linlin; Shen, Yan; Shen, Bo; Chen, Chen; Sun, Yimin; Wang, Jian; Tang, Yilin (Frontiers in Aging Neuroscience, 2020)
Background Quality of life (QoL) was worse in Parkinson’s disease patients with mild cognitive impairment (PD-MCI) or dementia (PDD) than PD patients with normal cognition (PD-NC). The aim of this study was to investigate and compare the potential heterogeneous determinants of QoL in PD patients with different cognitive statuses. Methods We recruited 600 PD patients, including 185 PD-NC patients, 336 PD-MCI patients and 79 PDD patients, in this cross-sectional study. All patients completed the QoL assessment by the 39-item Parkinson’s Disease Questionnaire (PDQ-39), as well as clinical evaluations and neuropsychological tests. The determinants of the QoL were analyzed by multiple stepwise regression analysis. Results QoL was more impaired across the three groups (PD-NC < PD-MCI < PDD). The Unified Parkinson’s Disease Rating Scale part III (UPDRS-III) score, Geriatric Depression Rating Scale (GDS) score and daily levodopa equivalent dose (LED) were independent variables of PDQ-39 in PD-NC patients. The GDS score, disease duration, UPDRS-III score, Epworth Sleepiness Score (ESS) and sex were independent variables of PDQ-39 in PD-MCI patients. The GDS score and disease duration were independent variables of PDQ-39 in PDD patients. Conclusion The determinants of QoL in PD-NC, PD-MCI and PDD patients were heterogeneous. Motor function was considered to be the most crucial determinant for QoL in PD-NC, while depression was indicated to be the most vital determinant for PD-MCI and PDD. For QoL improvement, clinicians might need to focus more on motor function in PD-NC patients and on depression in PD-MCI and PDD patients.